Costs, Revenue, and Business-Level Strategy - Jones, Gareth R.; Butler, John E. (Academy of Management Review, 1988)
There is an ongoing debate as to whether the strategies of differentiation and cost leadership are mutually exclusive or whether they can be achieved simultaneously. Using transaction cost theory, a model of business-level strategy is developed that reconciles these divergent perspectives. It is argued that when transaction costs, production costs, and revenue are considered within the calculus of a single model, the trade-offs a firm faces when choosing a business strategy become clearer.